Lean and Agile Project Management and the Challenges for its Implementation in SMEs in Czech Republic - Róbert Modranský; Jakabová, Silvia; Michal Hanák; Albert Oláh (Technium Social Sciences Journal, 2020)
The purpose of this paper is to investigate the possibilities, challenges and benefits of implementing Lean & agile project management in manufacturing SMEs. Lean & agile project management methods were originally developed for the software development industry, where they have revolutionized the way projects are managed. In the last decade, practitioners outside software development industry have started to realize the potential and benefits of implementing the agile approach. However, there are still only a few researches devoted to agile hardware development, and even fewer on the possibilities of its implementation in SMEs. By conducting a case study in the only manufacturing SMEs that has successfully implemented Scrum, analysing internal company’s documents and interviewing several employees and top managers from different sectors, who participated in the projects where Scrum was implemented, the lessons this organization has learned and that could be beneficial for both researchers and practitioners, are reported. The findings from this research show that although some adaptions of the Scrum framework were required, the applicability of the Scrum in this manufacturing SME was possible and beneficial.